Calidad de servicio y satisfacción al cliente en el "Hostal Scorpio" en la ciudad de Trujillo 2018 - Miranda Bazán, Juan Jesús (2018)
The objective of this research was to determine to what extent the quality of service is related to customer satisfaction in the Hostal Scorpio, Trujillo 2018. The sample was for convenience, and consisted of 90 guests. As an instrument, the SERVQUAL questionnaire modified and adapted by Cabello and Chirinos (2010) was used. The results allow us to conclude: the quality of service from the perspective of the guest in the Scorpio, Trujillo 2018 a 61% i qualify it without quality, and only 39% qualify it with quality. The dimensions that most influenced this result were the response capacity that I qualify with a 80% without quality, another dimension that contributed were the tangible aspects with a 61% of dissatisfaction. Regarding the satisfaction of the hosting service, a 61% of the sample I qualify as not satisfied, while 31% i qualify it satisfied, and 8% was very satisfied. The dimensions that contributed to very satisfied were empathy (26% very satisfied) and reliability (22% very satisfied) this is important because the empathy does not depend on the client but the one who attended it. On the other hand the dimension that most contributed to the high dissatisfaction was the capacity of response that has to do also with the staff, because in this same dimension 9% were very satisfied. It was statistically demonstrated that there is a significant relationship between the quality of attention and customer satisfaction, so it is inferred that to improve the quality of care in Hostal Scorpio, it is necessary to improve customer satisfaction.